Pengaruh Pengungkapan Corporate Social Reponsibility Terhadap Nilai Perusahaan Sub Sektor, Restaurant, Hotel, Tourism, Advertising Dan Media - Monica Hendrik; Juniarti Juniarti Juniarti (Business Accounting Review, 2016)
The objective of this research was to find out whether or not Corporate Social Responsibility (CSR) had influence on the firm value. The CSR variable was measured based on the Global Reporting Initiatie 3.1 standard, while firm value was measured by using Tobin’s Q. The sample was taken from 108 companies years in hospitality, restaurant, tourism, advertising, and media sectors within 2009-2013. The result of this research showsed that Corporate Social Responsibility had no significant influence on the firm value, while the other control variables like firm size, market share, and debt to equity ratio had significant influence on firm value, where both firm size and DER had negative influence on the firm value, while market share had positive influence on the firm value.